Long-term exposure to black carbon, cognition and single nucleotide polymorphisms in microRNA processing genes in older men. (March 2016) - Colicino, Elena; Giuliano, Giulia; Power, Melinda C.; Lepeule, Johanna; Wilker, Elissa H.; Vokonas, Pantel; Brennan, Kasey J.M.; Fossati, Serena; Hoxha, Mirjam; Spiro, Avron; Weisskopf, Marc G.; Schwartz, Joel; et al.
Abstract: Introduction: Air pollution exposure has been linked to impaired cognitive aging, but little is known about biomarkers modifying this association. MicroRNAs (miRNAs) control gene expression and neuronal programming. miRNA levels vary due to single nucleotide polymorphisms (SNPs) in genes processing miRNAs from precursor molecules. Objectives: To investigate whether SNPs in miRNA-processing genes are associated with cognition and modify the relationship between black carbon (BC), marker of traffic-related pollution, and cognitive functions. Methods: 533 Normative Aging Study men (mean ± SD 72 ± 7 years) were tested ≤ 4 times (mean = 1.7 times) using seven cognitive tests between 1995 and 2007. We tested interactions of 16 miRNA-related SNPs with 1-year average BC from a validated land-use-regression model. We used covariate-adjusted logistic regression for low (≤ 25) Mini-Mental tate Examination (MMSE) and mixed-effect regression for a global cognitive score combining six other tests. Results: Global cognition was negatively associated with the homozygous minor variant of rs595961 AGO1 (− 0.42SD; 95%CI: (− 0.71, − 0.13)) relative to the major variant. BC-MMSE association was stronger in heterozygous carriers of rs11077 XPO5 (OR = 1.99; 95%CI: (1.39, 2.85)) and minor variant carriers of GEMIN4 rs2740348 (OR = 1.34; 95%CI: (1.05, 1.7)), compared to their major variant. The BC-global-cognition association was stronger in heterozygous carriers of GEMIN4 rs4968104 (− 0.10SD; 95%CI: (− 0.18, − 0.02)), and GEMIN4 rs910924 (− 0.09SD; 95%CI: (− 0.17, − 0.02)) relative to the major variant. Blood miRNA expression analyses showed associations only of XPO5 rs11077 with miR-9 and miR-96. Conclusions: Carriers of particular miRNA-processing SNPs had higher susceptibility to BC in BC–cognition associations, possibly due to influences on miRNA expression. Highlights: Black carbon (BC), marker of air pollution, was adversely associated with cognition. SNPs in miRNA processing-genes were adversely associated with cognition. SNPs in miRNA processing-genes affected susceptibility to BC–cognition association. Susceptibility possibly due to influences on miRNA expression